After the Cure : the Untold Stories of Breast Cancer Survivors. - Abel, Emily K. (NYU Press, 2008)
2009 Choice Outstanding Academic Title. 2009 Association of American University Presses Award for Jacket Design. Chemo brain. Fatigue. Chronic pain. Insomnia. Depression. These are just a few of the ongoing, debilitating symptoms that plague some breast-cancer survivors long after their treatments have officially ended. While there are hundreds of books about breast cancer, ranging from practical medical advice to inspirational stories of survivors, what has been missing until now is testimony from the thousands of women who continue to struggle with persistent health problems. After the Cure.